Model-based planning of technical building services and process chains for battery cell production. (10th October 2022) - Vogt, Marcus; Dér, Antal; Khalid, Usama; Cerdas, Felipe; Herrmann, Christoph
Abstract: Heating, ventilation and air conditioning (HVAC) systems in battery production are a main component of the technical building services (TBS) and ensure the required low moisture conditions in dry rooms for battery cell assembly. In fulfilling these functions, they contribute significantly to the overall energy demand and are among the main energy consumers in battery production. In this context, model-based approaches to support the sizing and planning of these systems are increasingly interesting, as they enable the consideration of the system dynamics of the involved components. Furthermore, few data with regard to energy requirements of TBS in the context of battery cell production is available. We propose in this paper a 5-step planning procedure to address both of these problems. The planning procedure structures the planning process for the design of relevant TBS components in the context of battery cell production by using an inside-out planning approach. Moreover, we publish in this paper comprehensive data sets to evaluate the energy demand of battery cell production in dry rooms at 22 different locations and 10 different plant size with three different internal loads of moisture and heat per size and explain how to use the proposed procedure in this case. Our planning procedure enables planners to better size HVAC systems and evaluate alternative system designs in the context of battery cell production. We illustrate the application of the planning procedure with a case study. The goals of the case study are to assess, whether the air or cooling supply should be centralized or decentralized and to correctly dimension the TBS to supply the two dry rooms using the proposed planning procedure. The results of the case study show that the supply of the dry room with conditioned air via the HVAC system should be realized using two decentralized HVAC system, which saves up to 7.4% of final energy compared to the centralized variant. However regarding the cooling supply, constant base loads of min. 15 % occur through-out the year and since modern chillers usually have high efficiencies at partial load, a central supply is preferable for the cooling supply. The provided data sets of the 660 considered simulation cases can be used to assess the energetic demand to operate dry rooms for battery production at different locations, scales and internal loads, which is a considerable added value in the context of life-cycle assessment of the battery production. With the data sets, supply air volume flows of 5500 m 3 / h - 99000 m 3 / h can be considered, which covers plant sizes from laboratory to industrial size scales. Highlights: Model-based planning of technical building services for battery production Proposition of 5-step inside out planning procedure for technical building services. Evaluation of centralized and decentralized supply systems for dry room operation. Publication of data sets to evaluate 660 cases at different locations, scales and internal loads of dry rooms. Provision of evaluation scripts to simplify the assessments from user's point of view.